2021
DOI: 10.33137/ijidi.v5i4.37406
|View full text |Cite
|
Sign up to set email alerts
|

Crisis of Erasure

Abstract: In this paper, we use the topic of breast cancer as an example of health crisis erasure in both informational and institutional contexts, particularly within the transgender and gender-nonconforming population. Breast cancer health information conforms and defaults to conventional cultural associations with femininity, as is the case with pregnancy and other “single-sex” conditions (Surkan, 2015). Many health information and research practices normalize sexualities, pathologize non-normative gender (Drescher e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…This pattern of isolating identities is further observed when considering the representation of diverse gender identities within the articles included in this analysis. Despite TGE individuals being included in the LGBT umbrella label, scientific literature, media, and health promotion efforts continue to neglect TGE individuals' experiences, as does sex-positive research (Tenney et al, 2021). For instance, research that nominally includes TGE individuals under the LGBT umbrella often fails to acknowledge how experiences of gender (specifically gender-confirming hormone and surgical interventions) can impact pleasure through masturbation, frequency of engaging in sexual activities, and sexual desire (Nikkelen & Kreukels, 2018).…”
Section: Sex-positive Research Among Plurisexual Populations Underrep...mentioning
confidence: 99%
“…This pattern of isolating identities is further observed when considering the representation of diverse gender identities within the articles included in this analysis. Despite TGE individuals being included in the LGBT umbrella label, scientific literature, media, and health promotion efforts continue to neglect TGE individuals' experiences, as does sex-positive research (Tenney et al, 2021). For instance, research that nominally includes TGE individuals under the LGBT umbrella often fails to acknowledge how experiences of gender (specifically gender-confirming hormone and surgical interventions) can impact pleasure through masturbation, frequency of engaging in sexual activities, and sexual desire (Nikkelen & Kreukels, 2018).…”
Section: Sex-positive Research Among Plurisexual Populations Underrep...mentioning
confidence: 99%
“…Recent studies have focused on health information seeking by sexual and gender minority youth and information seeking by men who have sex with men (MSM) on topics such as pre-exposure prophylaxis (PrEP), a medication that decreases the risk of HIV transmission [25,26,27]. Other studies have focused on information seeking by transgender and gender diverse persons, in areas such as breast cancer screening and human papillomavirus vaccination [28,29]. In a library-centered study, Drake and Bielefield reported on the information needs of transgender library patrons.…”
Section: Introductionmentioning
confidence: 99%